2020
DOI: 10.1192/j.eurpsy.2020.94
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk in patients with severe mental illness in Italy

Abstract: Background: Patients with severe mental illness (SMI), such as schizophrenia or bipolar disorders, are more frequently affected by metabolic syndrome and cardiovascular (CV) diseases than the general population, with a significant reduction in life expectancy. Beyond metabolic syndrome, quantifying the risk of CV morbidity in the long-term may help clinicians to put in place preventive strategies. In this study we assessed 10-year CV risk in patients with SMI and healthy individuals using an algorithm validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
(40 reference statements)
3
7
0
2
Order By: Relevance
“…BD represents a leading cause of burden worldwide and contributes significantly to premature death [ 2 ]. Subjects with BD are at high risk of presenting with co-occurrent psychiatric illnesses, including alcohol and substance use disorders [ 3 , 4 , 5 ], as well as serious medical comorbidities [ 3 , 6 , 7 , 8 , 9 , 10 ]. Moreover, suicide risk is up to 30 times higher in individuals with BD than the general population, with one in four to five subjects attempting suicide lifetime [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…BD represents a leading cause of burden worldwide and contributes significantly to premature death [ 2 ]. Subjects with BD are at high risk of presenting with co-occurrent psychiatric illnesses, including alcohol and substance use disorders [ 3 , 4 , 5 ], as well as serious medical comorbidities [ 3 , 6 , 7 , 8 , 9 , 10 ]. Moreover, suicide risk is up to 30 times higher in individuals with BD than the general population, with one in four to five subjects attempting suicide lifetime [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…MetS is a clustering of at least three of the following five medical conditions: abdominal obesity, high blood pressure, high blood glucose, high serum triglycerides, and low serum high-density lipoprotein (HDL). The prevalence of MetS increases the risk of developing both cardiovascular disease and type 2 diabetes [11,12]. A meta-analysis by Vancampfort et al reported that the overall MetS prevalence in patients with BD was 37.3% [13].…”
Section: Introductionmentioning
confidence: 99%
“…Scientific evidence obtained in American and Italian studies addressing the physical harm caused by smoking among people with mental disorders shows that smoking is one of the factors associated with the reduction in the life expectancy of this population and the high prevalence of somatic comorbidities (20)(21) . During the COVID-19 pandemic, European authors revived this discussion, expressing that smoking is an important risk factor for COVID-19 complications in this population (22) .…”
Section: Resultsmentioning
confidence: 99%